2017
DOI: 10.1002/jcb.25874
|View full text |Cite
|
Sign up to set email alerts
|

Lnk Deficiency Leads to TPO-Mediated Osteoclastogenesis and Increased Bone Mass Phenotype

Abstract: The Lnk adapter protein negatively regulates the signaling of thrombopoietin (TPO), the main megakaryocyte (MK) growth factor. Lnk-deficient (−/−) mice have increased TPO signaling and increased MK number. Interestingly, several mouse models exist in which increased MK number leads to a high bone mass phenotype. Here we report the bone phenotype of these mice. MicroCT and static histomorphometric analyses at 20 weeks showed the distal femur of Lnk−/− mice to have significantly higher bone volume fraction and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…A co-culture experiment of MKs with murine calvarial osteoblasts showed improvements in osteoblast proliferation by three- to six-fold, compared to control groups, osteoblasts cultured alone [ 114 ]. Other studies have demonstrated that MKs are vital in osteoclast formation [ 114 , 115 , 116 , 117 , 118 , 119 ]. In addition, osteoclasts are essential in bone remodeling and eliminate necrotic tissue in the early phases of bone repair [ 120 , 121 ].…”
Section: Inducing Mks Via Thrombopoietin: a Potential Therapy For Craniofacial Bone Defectsmentioning
confidence: 99%
See 1 more Smart Citation
“…A co-culture experiment of MKs with murine calvarial osteoblasts showed improvements in osteoblast proliferation by three- to six-fold, compared to control groups, osteoblasts cultured alone [ 114 ]. Other studies have demonstrated that MKs are vital in osteoclast formation [ 114 , 115 , 116 , 117 , 118 , 119 ]. In addition, osteoclasts are essential in bone remodeling and eliminate necrotic tissue in the early phases of bone repair [ 120 , 121 ].…”
Section: Inducing Mks Via Thrombopoietin: a Potential Therapy For Craniofacial Bone Defectsmentioning
confidence: 99%
“…TPO induce HSCs to differentiate into mature MKs which are ultimately producing platelets, Figure 2 [ 104 , 105 , 106 , 107 , 110 , 111 ]. Several studies demonstrate that MKs play a key role in osteoblast proliferation [ 108 , 112 , 113 , 114 , 115 ] and osteoclast formation [ 114 , 115 , 116 , 117 , 118 , 119 ]. Osteoblasts and osteoclasts are essential for bone remodeling and eliminating necrotic tissue in early bone repair [ 120 , 121 ].…”
Section: Introductionmentioning
confidence: 99%
“…in regulating the activity of osteoblasts and osteoclasts [5][6][7][8]. One cell type of particular interest is the MK, which plays a role in the regulation of bone formation and bone resorption within the marrow cavity [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous mouse models have been made where MK numbers are increased. These mice also have greatly increased bone growth within the marrow cavity [9,10,[20][21][22][23][24][25][26][27]. Importantly, osteosclerosis has been documented in patients with megakaryocytoses [28,29].…”
Section: Introductionmentioning
confidence: 99%
“…Regarding bone formation, several animal models with increased MK have also shown to exhibit increased bone formation 16 ; the increased osteoblast proliferation by MKs mainly mediated it [16][17][18] . Eventually, the mouse models with increased MK number exhibited the osteosclerotic phenotype 12,16,[19][20][21][22][23][24][25] . Thus, MK plays an of trabecular bone, regions of interest (ROI) of cancellous bone were created within the endosteal envelope on the two-dimensional slices.…”
mentioning
confidence: 99%